Investigation on the efficiency of Brucea javanica oil emulsion injection with chemotherapy for treating malignant pleural effusion: A meta-analysis of randomized controlled trials - Shi, Rui; Wu, Zhishan; Wang, Haojia; Zhang, Jingyuan; Zhang, Fanqin; Stalin, Antony; Chen, Meilin; Huang, Jiaqi; Zhai, Yiyan; Zhang, Qianqian; Liu, Pengyun; Wu, Jiarui; et al. (Frontiers in pharmacology, 2022)
Introduction: Systematic evaluation of the clinical efficacy and safety of Brucea javanica oil emulsion injection (BJOEI) in combination with chemotherapy in the treatment of malignant pleural effusion (MPE). Methods: The study searched CNKI, Wanfang database, VIP database, SinoMed, PubMed, Embase, the Cochrane Library, and the Web of Science database and retrieved randomized controlled trials (RCTs) on the treatment of MPE with BJOEI in combination with chemotherapy from seven electronic databases from inception to 31 March 2022. Meta-analysis and sensitivity analysis were performed using Revman 5.4 and Stata 13.0 software. Results: Ultimately, 30 RCTs with 2035 patients were included, including 1002 cases in the control group and 1033 cases in the treatment group. The results of the meta-analysis showed that the overall efficacy rate of BJOEI combined with chemotherapy was higher in the treatment of MPE compared with chemotherapy alone ( RR = 1.45, 95%CI : 1.36–1.54, p < 0.00001). And it could improve the Karnofsky (KPS) score ( RR = 1.54, 95%CI : 1.41–1.68, p < 0.00001), reduce adverse reactions such as fever ( RR = 0.82, 95%CI:0.60–1.12), chest pain ( RR = 0.90, 95%CI : 0.67–1.21), gastrointestinal reactions ( RR = 0.70, 95%CI : 0.57–0.87, p < 0.005), and leukopenia ( RR = 0.51, 95%CI : 0.43–0.61, p < 0.00001). Conclusion: BJOEI combined with chemotherapy has better clinical efficacy than chemotherapy alone in the treatment of MPE. It can further improve KPS score, improve patients’ quality of life, and reduce the occurrence of adverse reactions. However, the conclusions of this study need to be confirmed by further randomized, double-blind, controlled trials with large sample size, reasonable design, and strict implementation.